Inhibition of bactericidal activity of anticapsular antibody by nonspecific antibodies reactive with surface-exposed antigenic determinants on Actinobacillus pleuropneumoniae. - Udeze, F A (1992)
In an attempt to understand the mechanism of serum resistance in Actinobacillus pleuropneumoniae, in the present study we examined various interactions among the bacterial surface constituents, serum antibodies, and complement. Analysis of swine sera revealed the presence of anticapsular antibodies in convalescent-phase sera but not in preimmune sera. Both types of sera contained antibodies which reacted with each of 14 polypeptides present in saline extracts of the bacteria. Absorption of the preimmune sera with intact bacteria depleted antibodies to two of the polypeptides (27 and 32 kDa) and high-molecular-weight (greater than 97.4,000) components which did not stain with Coomassie blue. Data derived from complement consumption and C3-binding experiments indicated that the organism was capable of initiating complement activation and binding C3 during incubation in preimmune and immune sera. Experiments designed to evaluate the bactericidal effectiveness of anticapsular antibody revealed that the purified antibody was bactericidal only when preimmune sera absorbed with intact bacteria were used as a source of complement. The bactericidal effects of anticapsular antibody and absorbed preimmune sera were inhibited in a dose-dependent manner by heat-inactivated preimmune sera and immunoglobulin G derived from the sera. The inhibitory activity of the preimmune sera was neutralized by preincubating the sera with column fractions of the saline extract which contained either the 27- or the 32-kDa polypeptide. These results indicate that serum resistance in A. pleuropneumoniae 4074 could be related to inhibition of the bactericidal action of anticapsular antibody by nonspecific antibodies which recognize surface-exposed epitopes on the polypeptides.